Integrating Social Innovation into the Curriculum of Higher Education Institutions in Latin America: Insights from the Students4Change Project - Unceta, Alfonso; Guerra, Igone; Barandiaran, Xabier (Sustainability, 2021)
In the last two decades, social innovation (SI) and social entrepreneurship (SE) have gained relevance and interest within the framework of academia at international level. Higher education institutions (HEIs) are key players in promoting innovation and social entrepreneurship initiatives that respond to multifaceted challenges. They support strategies on the basis of the strengthening of participation, collaboration, and cooperation with society and its local communities. However, the approach of Latin American universities to SI and SE has been very uneven in the way they have understood them, integrated them into academic programmes, and transferred knowledge to society. On the basis of the experience of the Students4Change project, we sought to understand the role of Latin American HEIs in promoting social innovations by analysing the experiences of 10 participating universities to formalise a pedagogical programme on SI and SE in their institutions. The results suggest that there is still a need to formalise an academic syllabus that is speciﬁcally designed to promote social innovations and to train universities in this endeavour. This paper contributes to the identiﬁcation of the main levers of change, strengths, and challenges that Latin American universities face to institutionalise SI and SE in their contexts.
Keywords: Amérique latine; Libre accès; Rôle des universités

Integrating Social Innovation into the Curriculum of Higher Education Institutions in Latin America: Insights from the Students4Change Project - Unceta, Alfonso; Guerra, Igone; Barandiaran, Xabier (Sustainability, 2021)
In the last two decades, social innovation (SI) and social entrepreneurship (SE) have gained relevance and interest within the framework of academia at international level. Higher education institutions (HEIs) are key players in promoting innovation and social entrepreneurship initiatives that respond to multifaceted challenges. They support strategies on the basis of the strengthening of participation, collaboration, and cooperation with society and its local communities. However, the approach of Latin American universities to SI and SE has been very uneven in the way they have understood them, integrated them into academic programmes, and transferred knowledge to society. On the basis of the experience of the Students4Change project, we sought to understand the role of Latin American HEIs in promoting social innovations by analysing the experiences of 10 participating universities to formalise a pedagogical programme on SI and SE in their institutions. The results suggest that there is still a need to formalise an academic syllabus that is speciﬁcally designed to promote social innovations and to train universities in this endeavour. This paper contributes to the identiﬁcation of the main levers of change, strengths, and challenges that Latin American universities face to institutionalise SI and SE in their contexts.
Number: 10
Keywords: Amérique latine; Libre accès; Rôle des universités

LES MODES D’INNOVATION SOCIALE ET DE GOUVERNANCE - Castro-Spila, Javier; Unceta, Alfonso (La transformation sociale par l'innovation sociale, 2016)
La relation entre l’innovation sociale et la gouvernance n’est pas suffisamment explorée dans la littérature scientifique. Les analyses que l’on trouve sur ce sujet se rapportent principalement à la relation entre l’administration publique, la participation citoyenne, le changement social et les nouvelles formes de gouvernance (Lévesque, 2012 ; Moulaertet al., 2007 ; Novy, Hamme et Leubolt, 2009). Dans ces approches, l’innovation sociale est abordée comme le rapport entre les relations sociales et la gouvernance. Ainsi, cette perspective cherche plutôt à comprendre comment certains groupes sociaux développent leurs capacités sociopolitiques pour garantir leur accès aux ressources qui permettent de répondre

LES MODES D’INNOVATION SOCIALE ET DE GOUVERNANCE - Castro-Spila, Javier; Unceta, Alfonso (La transformation sociale par l'innovation sociale, 2016)
La relation entre l’innovation sociale et la gouvernance n’est pas suffisamment explorée dans la littérature scientifique. Les analyses que l’on trouve sur ce sujet se rapportent principalement à la relation entre l’administration publique, la participation citoyenne, le changement social et les nouvelles formes de gouvernance (Lévesque, 2012 ; Moulaertet al., 2007 ; Novy, Hamme et Leubolt, 2009). Dans ces approches, l’innovation sociale est abordée comme le rapport entre les relations sociales et la gouvernance. Ainsi, cette perspective cherche plutôt à comprendre comment certains groupes sociaux développent leurs capacités sociopolitiques pour garantir leur accès aux ressources qui permettent de répondre